2022
DOI: 10.1038/s41420-022-01059-5
|View full text |Cite
|
Sign up to set email alerts
|

Taraxasterol prompted the anti-tumor effect in mice burden hepatocellular carcinoma by regulating T lymphocytes

Abstract: Hepatocellular carcinoma (HCC) is a common digestive malignant tumor with high morbidity and mortality worldwide, however, the treatment of HCC and prognosis of patients are not optimistic, finding more effective treatments are imperative. Taraxacum officinale (L.) Weber ex F.H.Wigg is a perennial herb of compositae, and our study has demonstrated that Taraxacum officinale polysaccharide has certain anti-tumor effect on HCC cells. Taraxasterol (TS) is a natural product extracted from Taraxacum officinale with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Wen-Ting Fei et al reported that the mechanism of immunomodulatory effect of Maca polysaccharides was related to inhibiting lymphocyte apoptosis and promoting the balance of Th1/Th2 cell subsets [ 16 ]. Taraxasterol regulated the immunity of H22 bearing mice by elevating the ratio of CD4 + T cells in the spleen, and increasing the number of T cell infiltration in tumor tissue [ 27 ]. But due to the lack of easily detectable light-emitting groups, further research on polysaccharides has always been hindered.…”
Section: Discussionmentioning
confidence: 99%
“…Wen-Ting Fei et al reported that the mechanism of immunomodulatory effect of Maca polysaccharides was related to inhibiting lymphocyte apoptosis and promoting the balance of Th1/Th2 cell subsets [ 16 ]. Taraxasterol regulated the immunity of H22 bearing mice by elevating the ratio of CD4 + T cells in the spleen, and increasing the number of T cell infiltration in tumor tissue [ 27 ]. But due to the lack of easily detectable light-emitting groups, further research on polysaccharides has always been hindered.…”
Section: Discussionmentioning
confidence: 99%
“…The study of plant lignans and phytochemicals, which are thought to be the cause of these effects, has dominated research on the therapeutic benefits of roots up until this point. While effects of these products on “ immune boosting’ have been reported extensively (e.g Burdock root ( Chan et al, 2011 ; He et al, 2018 ; Suzuki et al, 2002 ; Wang and Yang, 1993 ), Essiac (1998) Kava Kava Root ( Minh et al, 2022 ; Pont-Fernandez et al, 2022 ), Butchers broom ( Masullo et al, 2016 ; Rodrigues et al, 2021 ) Dandelion Root ( Ren et al, 2022 ; Talapphet et al, 2021 ) and Pleurisy Root ( Warashina and Noro, 2010 ), the plants microbiome has not been investigated in the way that would be most appropriate. Further study into relevance of the microbiome of plant will likely unveil it to be a most significant influencer of immune system response.…”
Section: Rootsmentioning
confidence: 99%
“…Taraxacum officinale (L.) Weber ex F.H. Wigg, a perennial member of the Compositae family, has antitumor properties in HCC cells and has long been conventionally used as Chinese herbal medicine for liver, breast and gallbladder, hepatitis, as well as digestive, diseases [ 323 ]. According to the US Food and Drug Administration, the medication for HCC first-line therapies are bevacizumab in combination with atezolizumab, Sorafenib, and Lenvatinib; the second-line therapies include cabozantinib, pembrolizumab, ramucirumab, and regorafenib, in addition to other agents, such as bevacizumab, nivolumab, and nivolumab in combination with ipilimumab [ 324 ].…”
Section: Lncrnas As Diagnostic and Therapeutic Markers In Hccmentioning
confidence: 99%